3(n-3)=-42

Simple and best practice solution for 3(n-3)=-42 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(n-3)=-42 equation:


Simplifying
3(n + -3) = -42

Reorder the terms:
3(-3 + n) = -42
(-3 * 3 + n * 3) = -42
(-9 + 3n) = -42

Solving
-9 + 3n = -42

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '9' to each side of the equation.
-9 + 9 + 3n = -42 + 9

Combine like terms: -9 + 9 = 0
0 + 3n = -42 + 9
3n = -42 + 9

Combine like terms: -42 + 9 = -33
3n = -33

Divide each side by '3'.
n = -11

Simplifying
n = -11

See similar equations:

| 150(225+3.5x)=2000 | | 3x^2+2y=o | | 4(6m+7)+2(3m-6)= | | 12-15y=4 | | x^8-2x^4+1= | | 4W+28=16v | | 25x^2+100x+200=0 | | 3(x+12)=3x | | 17x-5=80 | | K^2=200 | | 4x+20=2(3x) | | A=3x+6 | | 5n+4-8h=-5 | | -4(m-6)=-48 | | -9-7n=-5 | | -3(-2g+16)= | | .75x-.33x=9 | | -2(-8+3c)= | | 3(g+3)=24 | | 3(10)-5y=20 | | (5u-3)(4+u)=0 | | 7-2(-5x-9)+2x=4(2x-1)+3x+2 | | -11(16-13z)= | | 9-9r=-8 | | 15+3z=39 | | -6-3x=40-5x | | -4(-6-16k)= | | -35y=20 | | 3x+4(3x-53)=7 | | 5x-(2x-9)=18 | | 18(-6p-7)= | | 17x-5+80=180 |

Equations solver categories